Librarian and Traditional Knowledge : A Study Of Urgency and The Role Of Librarian In Traditional Knowledge - Adelia, Nisa (Universitas Airlangga, 2016)
Indonesia is an archipelago country which is rich of cultural treasures. These cultural treasuresinclude moral value, knowledge and technology that are used hereditary in local tradition. Most of these hereditary habits are done by oral tradition, so it less of documentations. Library as information center and has function as information provider, Willy Nilly, librarian has responsibility to preserve the knowledge of traditional culture as intellectual property. Besides that, the documentation activity will become cultural defense of Indonesia, so it can be used by the next generation for learning activity. View the significant of cultural documentation activity, this paper wants to discuss about the role of librarian in traditional knowledge.This type of research is study literature research. The writters will use a variety of literature that discusses about traditional knowledge. Then, they do the assessment about of the role of librarians to traditional knowledge.